Evaluation of Left Atrial Function in Patients with Paroxysmal Atrial Fibrillation Using Left Atrial Automatic Myocardial Functional Imaging Ultrasonography - Hailan Liu; Lili Chen; Yan Song; Yingying Xu; Chunquan Zhang (Cardiology Research and Practice)
Aim. To evaluate volume and strain of the left atrium (LA) in people suffering from paroxysmal atrial fibrillation which is not valvular (NVPAF) using the new technology of left atrial automatic myocardial function imaging (AFILA) and to analyze prognostic factors in patients with NVPAF by follow-up. Methods. Between August 2019 and August 2022, a total of 80 NVPAF patients and 60 normal control patients who were hospitalized in the Department of Cardiology were included in the study. The LA volume and strain parameters of the two groups were analyzed. The differences in LA function (LAF) parameters were compared between the two groups to generate the receiver operating characteristic curve (ROC) and calculate the area under the curve (AUC), sensitivity, and specificity of each parameter. Follow-up was conducted on the 80 NVPAF patients included, their treatment methods after admission and their rehospitalization due to heart events were recorded, and independent risk factors influencing the prognosis of NVPAF were obtained. Results. A total of 140 patients participated in the study, including 80 in the NVPAF group and 60 in the normal control group. There was no statistically significant difference in age and sex between the two groups. Compared to the normal group, the LA minimum volume (LAVmin), LA maximum volume (LAVmax), and volume at onset of LA contraction (LAVpreA) in the NVPAF group were significantly increased. The LA emptying fraction (LAEF) was significantly decreased, and LA reservoir strain (S_R), LA conduit strain (S_CD), and LA contractile strain (S_CT) were significantly compromised (P < 0.05). There was no significant difference in LA evacuation volume (LAEV) reduction (P > 0.05). Logistic regression analysis of LAF parameters in NVPAF patients showed that LAEF and S_R were independently correlated with NVPAF (odds ratio values: 0.883 (0.827–0.943), P < 0.001; 0.916 (0.569–1.474), P = 0.047). The ROC curve results showed that LAEF had a high efficiency in the diagnosis of NVPAF, with P < 0.001, AUC of 0.843, sensitivity of 0.788, and specificity of 0.867. For the LA strain parameters, the S_R test efficiency was higher, with P < 0.001, AUC of 0.762, sensitivity of 0.713, and specificity of 0.783. There was a strong correlation between S_R and LAEF in patients with no end event and those with end event. The ROC curve revealed that the S_R was better than LAEF in predicting prognosis of patients with AF (AUC = 0.914, P < 0.0001 vs. AUC = 0.876, P < 0.0001). S_R of 10.5 and LAEF of 21 were the cut-off values for endpoint events in NVPAF patients, with sensitivity of 0.909 and 0.727 and specificity of 0.904 and 0.901, respectively. Conclusions. AFILA ultrasound technology comprehensively evaluated the LA size and function in patients with NVPAF. The LAEF and S_R were independently correlated with NVPAF and can determine the prognosis of patients with NVPAF.